Successful Businesses in Sukabirus Food Court - Feti Anggraeni; Imanuddin Hasbi (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
This research was conducted at the Sukabirus Food Court. Pujasera Sukabirus is a place to eat consisting of food counters offering a variety of varied menus. Sukabirus Food Court is an open and informal dining area. This business has been moving since the beginning of July 2018. Responding to this, this study aims to examine the effect of entrepreneurial motivation and entrepreneurial marketing on the success of businesses at food outlets in Sukabirus Food Court. The research uses quantitative research methods. This research uses sampling techniques on non-probability sampling, namely saturated sampling because members of the population amount to 30 people and the entire population is a sample. The sample in this study amounted to 30 respondents. Data collection in this study was conducted by distributing questionnaires distributed to all respondents namely, owners of food outlets in Sukabirus Food Court. Data analysis techniques used multiple regression analysis and descriptive analysis. The results showed that respondents' responses to entrepreneurial motivation in the good category with a score of 77.3%, respondents' responses to entrepreneurship marketing in the excellent category with a score of 70.31% and respondents' perception of business success in good categories with a score of 69.7%. The conclusion of this study is entrepreneurial motivation and entrepreneurial marketing have a positive and significant effect on business success with a score of 79.1%. These results can be interpreted that the increase in entrepreneurial motivation and entrepreneurial marketing in the Sukabirus Food Court business will have an effect on increasing business success. Keywords: business success, entrepreneurial marketing, entrepreneurship motivation, food court.